2022
DOI: 10.1002/mbo3.1268
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in silico screening for antimicrobial compounds from cyanobacteria

Abstract: Due to the emerging rise of multi‐drug resistant bacteria, the discovery of novel antibiotics is of high scientific interest. Through their high chemodiversity of bioactive secondary metabolites, cyanobacteria have proven to be promising microorganisms for the discovery of antibacterial compounds. These aspects make appropriate antibacterial screening approaches for cyanobacteria crucial. Up to date, screenings are mostly carried out using a phenotypic methodology, consisting of cyanobacterial cultivation, ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 78 publications
(144 reference statements)
0
0
0
1
Order By: Relevance
“…With regard to the molecular basis of bioactive compound production from cyanobacteria in general and Syenchococcus sp. in particular, Strieth et al [47] recommended the use of in silico alongside in vivo screening for antimicrobial compounds from cyanobacteria. Indeed, Konstantinou et al [48] screened marine cyanobacteria associated with sponge and found that three marine Syechococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the molecular basis of bioactive compound production from cyanobacteria in general and Syenchococcus sp. in particular, Strieth et al [47] recommended the use of in silico alongside in vivo screening for antimicrobial compounds from cyanobacteria. Indeed, Konstantinou et al [48] screened marine cyanobacteria associated with sponge and found that three marine Syechococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…This halogenase was investigated to uncover its natural substrates [76]. Other studies resulted in advances in the screening of cyanobacterial genomes, whether in vivo through PCR or in silico using genome-mining techniques [77].…”
Section: Metabolomics Metabolic Profiling and Functional Genomicsmentioning
confidence: 99%
“…Die Biomasse an sich kann dabei als Nahrungs(erga ¨nzungs)mittel [3], als Tierfutter oder Du ¨ngemittel dienen [4,5]. Weiterhin produzieren viele Cyanobakterien antimikrobielle Verbindungen, die potenziell neue Wirkmechanismen aufweisen und so zur Beka ¨mpfung von multiresistenten Keimen beitragen ko ¨nnten [6]. Ich bescha ¨ftige mich vor allem mit dem Potenzial terrestrischer Cyanobakterien, die neben CO 2 auch Stickstoff und Feinstaub binden und unter Rauchgas kultiviert werden ko ¨nnen [7].…”
Section: Mikroalgen -Die Kleinen Alltagsheldenunclassified